Spontaneous Achilles tendon ruptures treated with a mini-open technique: clinical and functional evaluation - de Carli, A.; Vadala, A.; Ciardini, R.; Iorio, R.; Ferretti, A. (The Journal of Sports Medicine and Physical Fitness, 2009)
AIM and METHODS: Spontaneous ruptures of the Achilles tendon are frequent among occasional and high level athletes. Despite the frequency of this problem, there is no agreement about the treatment of this pathology. The purpose of this study was to show the results of 20 consecutive patients (14 males and 6 females) surgically treated between 1995 and 2001 with a mini-open technique (mean follow-up: 52 months; range 20-95 months). Postoperatively, all these patients were assessed with a new functional scoring scale and a functional jumping test (Ergo-Jump Bosco System). RESULTS: A very low rate of minor complications have been reported and most of these patients are now practicing their favoured sport at the same pre-injury level. CONCLUSIONS: Mini open repair should be considered an excellent method of treatment of this pathology, with a very low rate of complications. The authors recommend this technique for young professional and occasional athletes.